Safety of GMP-compliant iPSC lines generated by Sendai virus transduction is dependent upon clone identity and sex of the donor - Kuczynska, Zuzanna; Neglur, Pawan Kumar; Metin, Erkan; Liput, Michal; Zychowicz, Marzena; Zayat, Valery; Krześniak, Natalia E.; Buzanska, Leonora; Kot, Marta (Folia Neuropathologica, 2024)
Human induced pluripotent stem cells (hiPSCs) are a potential source of somatic cells for cell therapies due to their ability to self-renew and differentiate into various cells of the body. To date, the clinical application of hiPSCs has been limited due to safety issues. The present study aims to standardize the safety procedure of the derivation of GMP-compliant induced pluripotent stem cell (iPSC) lines from human fibroblasts. The hiPSC lines were generated using the nonintegrative Sendai virus method to incorporate Yamanaka reprogramming factors (OCT3/4, SOX2, KLF4 and c-MYC) into cells. A constant temperature was maintained during the cell culture, including all stages of the culture after transduction with Sendai virus. Pluripotency was proved in six independently generated hiPSC lines from adult female (47 years old) and male (57 years old) donors’ derived fibroblasts via alkaline phosphatase live (ALP) staining, qPCR, and immunocytochemistry. The hiPSC lines showed a gradual decrease in the presence of the virus with each subsequent passage, and this reduction was specific to the hiPSC line. The frequency and probability of chromosomal aberrations in hiPSCs were dependent on both the iPSC clone identity and sex of the donor. In summary, the generation of hiPSC for clinical applications requires safety standards application (biosafety protocol, quality control of hiPSC lines, viral and genetic integrity screening) from the first stages of the clonal selection of hiPSC from the same donor.